Antidiabetic and antihyperlipidemic effects of a methanolic extract of Mimosa pudica (Fabaceae) in diabetic rats. Issue 1 (2nd January 2019) - Parasuraman, Subramani; Ching, Teoh Huey; Leong, Chong Hao; Banik, Urmila
ABSTRACT: Mimosa pudica (Fabaceae) is a perennial herb and this plant is reported to have anticonvulsant, antimicrobial, antioxidant, antiulcer, antiasthmatic and wound healing activities. Diabetes dyslipidemic effect of Mimosa pudica is not clear. Hence the study is planned to investigate the antidiabetic and antihyperlipidemic activities of methanolic extract of Mimosa pudica (MEMP) on streptozotocin-induced diabetes mellitus in Sprague-Dawley rats. Antidiabetic and antihyperlipidemic effects of a MEMP was studied at 125, 250 and 500 mg/kg body weight (BW). The antidiabetic potential of MEMP was compared with glibenclamide 20 mg/kg BW. The body weight of rats and blood glucose levels were monitored at regular intervals during the experiment. At the end of the study, the blood sample was collected from the rats for biochemical analysis and they were sacrificed and their organs were used for histopathological analysis. Throughout the study, the diabetic controls rats showed a significant increase in glucose level, total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL) and very-low-density lipoprotein (VLDL) when compared with that of control, whereas the animals treated with glibenclamide and MEMP showed a significant reduction in the levels of glucose, TG, LDL, and VLDL when compared with that of diabetic control. In conclusion, MEMP showed a significant antidiabetic and antihyperlipidemic activities in streptozotocin-induced diabetic rats.